2016
DOI: 10.1097/mrr.0000000000000182
|View full text |Cite
|
Sign up to set email alerts
|

Life dissatisfaction is associated with depression and poorer surgical outcomes among lumbar spinal stenosis patients: a 10-year follow-up study

Abstract: Life satisfaction is associated with overall somatic health and the short-term surgical outcome in lumbar spinal stenosis (LSS) patients. In this study, the long-term relationship between life satisfaction and the surgical outcome in LSS patients was investigated in a 10-year follow-up. This prospective clinical study included 102 LSS patients who underwent decompressive surgery. They completed a set of questionnaires first preoperatively and then 6 times postoperatively (at 3 and 6 months, and at 1, 2, 5 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…Patients with more severe anxiety and depression tended to have lower levels of psychology well‐being. This result is consistent with the findings of Vereckei et al () and Pakarinen et al (), which suggested a negative correlation between well‐being and depression. Family support, depression and well‐being were found to be significantly correlated.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Patients with more severe anxiety and depression tended to have lower levels of psychology well‐being. This result is consistent with the findings of Vereckei et al () and Pakarinen et al (), which suggested a negative correlation between well‐being and depression. Family support, depression and well‐being were found to be significantly correlated.…”
Section: Discussionsupporting
confidence: 93%
“…To summarise these findings, anxiety and depression were found to affect patients’ preoperative and postoperative well‐being; however, the severity of disability was found to only impact preoperative well‐being. A decade‐long longitudinal study of 72 patients with lumbar spinal stenosis conducted by Pakarinen et al () found that patients with a greater life satisfaction had a lower level of disability and depression; and depression and life satisfaction had a long‐term correlation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations